The South shaping the global future shopping - Gosovic, Branislav (New Delhi Konark Publishers, 2016)
This monograph offers a broad overview of a continuing South-North development encounter in the United Nations. It is especially intended for the students of the subject and for all who have little opportunity to gain knowledge of the essence of the developing countries decades-long collective efforts in the international arena vis-a-vis the tenacious North-dominated hegemonic world order, one deeply rooted in the age of colonialism and imperialism. This background knowledge and awareness is required in the Global South's continued struggle for development, for the protection of the developing countries' political and economic sovereignty, and for their efforts in the United Nations for democratization, equity and change in international political and economic relations.
Keywords: South-North Development